1993
DOI: 10.1016/s0886-3350(13)80275-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospectively randomized trial comparing the pseudoaccommodation of the AMO ARRAY multifocal lens and a monofocal lens

Abstract: A prospective trial was set up to compare pseudoaccommodation. Fifty patients were randomized into two groups. Group 1 comprised 25 patients who had a monofocal implant and a postoperative refractive aim of -0.3 to -1.3 diopter (D) spherical equivalent and an astigmatic component between 1.0 and 1.75 D cylinder. Group 2 comprised 25 patients who had a new multizone refraction style multifocal implant and a postoperative refractive aim of -0.5 to +0.5 D spherical equivalent and an astigmatic component of less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…This is consistent with the design and function of the zonal progressive multifocal lens and with earlier findings that multifocal IOLs help most patients read without spectacles. [11][12][13][14][15][16][17][18] Our study also demonstrated significantly better best corrected distance acuity with the multifocal IOL. This contradicts previous reports that showed better near vision with multifocal IOLs but only equally good distance Snellen acuity.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This is consistent with the design and function of the zonal progressive multifocal lens and with earlier findings that multifocal IOLs help most patients read without spectacles. [11][12][13][14][15][16][17][18] Our study also demonstrated significantly better best corrected distance acuity with the multifocal IOL. This contradicts previous reports that showed better near vision with multifocal IOLs but only equally good distance Snellen acuity.…”
Section: Discussionsupporting
confidence: 54%
“…[13][14][15]17,18 The difference was, however, mild and not significant clinically. The decrease in contrast sensitivity reported in our study and others 25 appears to be an acceptable compromise to enhanced near and functional vision.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…36,37 Zonal photorefractive keratectomy, 38 decentred laser in situ keratomileusis 39 and implantation of corneal inlays 40 represent more experimental methods targeted at the cornea. Multifocal IOLs based on either diffractive optics or zones of varying refractive power, divide incoming light into two or more focal points and allow up to 50 per cent of patients to attain spectacle independence, 41 however, due to their design, multifocal implants are frequently associated with poorer contrast sensitivity than monofocal IOLs [42][43][44] and an increased incidence of troublesome visual phenomena including glare and halos. 45,46 To avoid such disturbing visual effects and restore natural accommodative function, the ultimate goal in ongoing AIOL and presbyopia research is to refill the capsular bag with a substance able to mimic the behaviour of the youthful lens mass.…”
mentioning
confidence: 99%